Uncertainty and countervailing incentives in procurement - Garcia, Helena Laneuville Teixeira (2017)
This thesis develops a simple model to represent a procurement situation with two main features. The first is that the optimal level of production cannot be fully anticipated when suppliers build their plants due to demand shocks. The second is that producers competing for a supply contract typically have different technologies within an efficient frontier, characterized by a trade-off between the marginal cost of production and the fixed cost per unit of capacity. With this framework in mind, we investigate how the shape of the frontier and the distribution of shocks affect efficient technology choices when the planner knows firms' technologies (first-best) and when she doesn't (second-best). In addition, we characterize how and when a well established real-life mechanism such as a quasi-linear score auction may implement second-best social welfare. We find that, if there is a strict preference over technologies in first-best, a quasi-linear score auction may implement second-best allocations. However, there is a non-neglectable case in which countervailing incentives arise, i.e. firms' allocations may be distorted either upwards or downwards with respect to first-best depending on their technologies. In that case, the planner may optimally choose to hire more than one firm, and there is no quasi-linear score auction that provides the social welfare achieved in second-best.